Tropical vibes from Sri Lanka - cyclotides from Viola betonicifolia by transcriptome and mass spectrometry analysis. (July 2021) - Rajendran, Sanjeevan; Slazak, Blazej; Mohotti, Supun; Strömstedt, Adam A.; Göransson, Ulf; Hettiarachchi, Chamari M.; Gunasekera, Sunithi
Abstract: Cyclotides are an extremely stable class of peptides, ubiquitously distributed in Violaceae. The aim of the present study was to investigate the presence of cyclotides in Sri Lankan Violaceae plants, using combined tools of transcriptomics and mass spectrometry. New cyclotides were discovered for the first time in the wild flora of Sri Lanka, within Viola betonicifolia, a plant used in traditional medicine as an antimicrobial. Plant extracts prepared in small scale from Viola betonicifolia were first subjected to LC-MS analysis. Subsequent transcriptome de novo sequencing of Viola betonicifolia uncovered 25 new (vibe 1–25) and three known (varv A/kalata S, viba 17, viba 11) peptide sequences from Möbius and bracelet cyclotide subfamilies as well as hybrid cyclotides. Among the transcripts, putative linear acyclotide sequences (vibe 4, vibe 10, vibe 11 and vibe 22) that lack a conserved asparagine or aspartic acid vital for cyclisation were also present. Four asparagine endopeptidases (AEPs), Vb AEP1-4 were found within the Viola betonicifolia transcriptome, including a peptide asparaginyl ligase (PAL), potentially involved in cyclotide backbone cyclisation, showing >93% sequence homology to Viola yedoensis peptide asparaginyl ligases, Vy PALs. In addition, we identified two protein disulfide isomerases (PDIs), Vb PDI1-2, likely involved in cyclotide oxidative folding, having high sequence homology (>74%) with previously reported Rubiaceae and Violaceae PDIs. The current study highlights the ubiquity of cyclotides in Violaceae as well as the utility of transcriptomic analysis for cyclotides and their putative processing enzyme discovery. The high variability of cyclotide sequences in terms of loop sizes and residues in V. betonicifolia showcase the cyclotide structure as an adaptable scaffold as well as their importance as a combinatorial library, implicated in plant defense. Graphical abstract: 25 new cyclotides/acyclotides and three previously characterised cyclotides were identified in Viola betonicifolia (Vibe), a Sri Lankan plant used in traditional medicine, by transcriptomic and mass spectrometry analysis. The cysteines were reduced and alkylated followed by enzymatic digestion to confirm the cyclic cystine knot motif in cyclotides, exemplified by one of the new cyclotides, vibe 13. In addition, four asparagine endopeptidases (AEPs), including one peptide asparaginyl ligase-type (PAL-type) and two protein disulfide isomerases (PDIs), likely involved in cyclotide biosynthesis were identified in the transcriptome. Image 1 Highlights: 25 new cyclotide and acyclotide sequences were discovered using transcriptomic analysis. Four plant AEPs including one ligase presumably involved in cyclotide biosynthesis were identified. Two protein disulfide isomerases likely involved in oxidative folding of cyclotides were identified.